Novel Functional Materials Based on Cellulose - Qi, Haisong (SpringerBriefs in Applied Sciences and Technology,, 2017)
This Brief presents a review of new eco-friendly processes, design and applications for novel cellulose-based materials, including regenerated materials, composites, nanocellulose and cellulose derivatives. Application of these materials in smart textiles, packaging, energy storage, sensors, gas separations, tissue engineering and drug release are highlighted. .